PERAN SOSIOLOGI DALAM PENDIDIKAN DASAR: KONSEP, TEORI, DAN IMPLIKASINYA TERHADAP PERUBAHAN SOSIAL - Tiarani, Siti Dhinda; Neviyarni S; Zelhendri Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the significant role of sociology in elementary education, emphasizing its function not only as a medium of knowledge transmission but also as a catalyst for social change. The purpose of this research is to provide a comprehensive theoretical understanding of how sociological approaches can strengthen the function of education in shaping social values and encouraging societal transformation. Using a literature study method, this research synthesizes academic books, journal articles, and research reports related to basic sociology concepts, characteristics, major sociological theories, and their relevance to elementary education. The analysis was conducted using a descriptive-analytical approach, systematically linking theoretical concepts to real phenomena in educational settings. The results show that the integration of sociological theories—such as functionalism, conflict theory, symbolic interactionism, cultural reproduction, and social capital—enhances the role of elementary education as a key agent of socialization. Elementary schools, through collaborative learning, multicultural education, and community involvement, can foster critical thinking, empathy, and social awareness among students. Thus, elementary education, when designed through a sociological perspective, has the potential to shape a more just, democratic, and culturally rich society.